The Implementation of Character Education (Disciplinary) Policy in Madrasah Tsanawiyah Riyadhus Sholihin Megang Sakti Musi Rawas - Tamam Tamam (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
This study aims to determine the implementation of disciplinary character education policy in Madrasah Tsanawiyah Riyadhus Sholihin Megang Sakti Musi Rawas. This research is field research with a qualitative approach, so in collecting data, the author uses observation techniques, in-depth interviews, documentation, and data analysis using Miles and Huberman analysis, namely through the process of reduction, display, and verification. The results showed that the implementation of the discipline character education policy at Madrasah Tsanawiyah Ryadhus Sholihin was carried out by including character education values in the school curriculum and then socializing the curriculum to student guardians in the new school year. The conclusion of the research found that the implementation of disciplinary character education policy includes integration in self-development activities, subjects, and school culture. This research contributes scientific information regarding the implementation of disciplinary character education policies in schools both theoretically and practically.